Historical evolution and present status of general practice in Nepal - Hayes, Bruce; Shrestha, Ashis (Journal of General Practice and Emergency Medicine of Nepal, 2014)
In 1981, in the face of no post-graduate training programs, health policy makers realized that Nepal needed “generalist” physicians who could cope with the wide range of preventive and curative medicine required in rural areas. From discussions between His Majesty’s Government (HMG) and the University of Calgary, the Medical Doctorate in General Practice (MDGP) programme was launched in 1982 by the Institute of Medicine (IOM), Tribhuvan University and the Ministry of Health (MOH).